Technology providers and financial stability: Overview of risks and regulatory frameworks - Gene Amromin; Cindy Hull; Emma Weiss; Rebecca Chmielewski; Patty Cowperthwait; Brett Solimine; Kenechukwu Anadu; Falk Braeuning; Siobhan Sanders; Lorenzo Garza; Sam Schulhofer-Wohl; Amy Chapel; et al. (Federal Reserve Bank of Chicago, 2025)
Technology-focused Third-Party Service Providers (TPSPs) have become important players in the operations of financial institutions and the financial markets. This paper summarizes microand macro-prudential regulatory frameworks in place to address risks that TPSPs pose to the financial system. The key takeaways are as follows: First, in the U.S., TPSPs operate under limited comprehensive prudential regulatory oversight, aimed primarily at ensuring that their products are safe and resilient on an ongoing basis. Second, while banks rely on multiple TPSPs and hundreds of their services daily for their core banking businesses, U.S. banking supervisors have limited direct visibility into these activities and risks they may pose. Third, although the existing U.S. regulatory framework has some systemic risk considerations, there is no macroprudential structure in place for TPSP risks. Official bodies in other jurisdictions have developed macroprudential frameworks or high-level guidance to address TPSP risks, but their implementation in major economies is nascent at best. Finally, TPSPs are likely an important source of systemic vulnerability for financial institutions and financial markets, although vulnerabilities may be difficult to discern due to a need to assess the criticality of each activity performed by TPSPs and the concentration of TPSPs within that activity.
Keywords: G10; G23; G28; 330; financial stability; third-party service providers; cyber risks